194k views
5 votes
the following equation was solved incorrectly for x2(x - 3) + 7 = 62x - 3 + 7 = 62x + 4 = 62x = 2x = 1explain what mistake the student made, correct it and finish the equation correctly. show all work

1 Answer

2 votes

We want to solve the following equation


2\cdot(x-3)+7=6

First, we start by distributing the multiplication on the left side, so we have


2x-6+7=6

Note that if we compare this step to the second step of the given procedure, the mistake occured on the distribution of the multiplication. So, instead of writing -6, the mistake was to write -3.

Now, we continue to solve the equation from this point. First, we operate on the left side, so we get


2x+1=6

Now, we subtract 1 from both sides


2x=6-1=5

Then, we divide both sides by 2. So we get


x=(5)/(2)

User Michael Ilyin
by
5.0k points